Essence of Buddhism: Religious Tolerance and Love for Nature, Essential for Human Existence - Rana, Rita (Historical Journal, 2020)
This work aims to present the essence and the importance of Buddhism for human existence along with a brief introduction of the founder of Buddhism and the impact and influence of this religion on the human society. A fact that life or all that exists is dynamic or changing and that which does not exist is actually permanent or static. The focus of this work is to show that the ultimate truth is through experience, religion, the awareness of religioustolerance and its benefits to the human world. Another point of focus is on the path towards Enlightenment which is believed to be by detachment in life rather than attachment. It highlights the ‘Teachings of Buddha’ to have an open mind and sympathetic heart that gives light and warmth to wisdom and compassion.